Pengaruh Investasi Dan Ekspor Terhadap Pertumbuhan Ekonomi Serta Penyerapan Tenaga Kerja Provinsi Kalimantan Timur - Taufik, Muhammad; Rochaida, Eny; Fitriadi, Fitriadi (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 2, Agustus 2014 (pp. 83-198), 2015)
This research was aims to know the influence of investment and exports on economic growth and Labor recruitment of East Kalimantan Province. The research was analyzed by using model of analysis two lanes performed with SPSS software version 11.5 with data retrival based on primary data of investment, exports, economic growth and labor from BPS of East Kalimantan from 2003 until 2011. Based on analysis way substructure 1 model through F test, showed that the independent variables (investment and exports) have a significant influence on economic growth because the value of the probability of the F-statistic less than standard real (0,008 < 0,08). So it can be said that both free variables used in the model has a real influence on economic growth at 5% level of trust (a=0,05). On the sub structure 2 model, indicates that the three of independent variables (investment, exports, economic growth) has significant effects on the labor recruitment  because probability F statistic’s value is less than real standard used by (0,000 < 0,05). So it can be said which this third free variable has a significant influence to labor reqruitment at 5% level of trust (a=0,05).
Keywords: investment; export; economic growth; labor; East Kalimantan